Comparing levels of mediatization in television journalism: An analysis of political reporting on US and UK evening news bulletins. (October 2014) - Cushion, Stephen; Rodger, Hugh; Lewis, Rachel
This comparative content analysis study ( N  = 946) examines how far political news is mediatized in the US and UK by systematically exploring the conventions used in television news bulletins. According to many of our mediatization of politics indicators – which included sound and imagebites, lip flaps, journalistic visibility, 'wrapping up', live and interpretive news – broadcasters with the most public service responsibilities supplied the highest level of mediatized political news. Our study thus appears to challenge conventional academic wisdom that US journalistic interventionism is greater than other advanced Western democracies and that enhanced commercialization is a precursor to higher degrees of mediatization. We suggest that the form, structure and style of journalism should be understood more carefully by scholars when making sense of how far news is mediatized, since the greater length of UK television news conventions and the ability to 'go live' longer allowed journalists greater freedom to interpret politics.